2014
DOI: 10.1039/c4ob00076e
|View full text |Cite
|
Sign up to set email alerts
|

RNA–peptide conjugate synthesis by inverse-electron demand Diels–Alder reaction

Abstract: Here we report an efficient method for the synthesis of RNA-peptide conjugates by inverse-electron demand Diels-Alder reaction. Various dienophiles were enzymatically incorporated into RNA and reacted with a chemically synthesized diene-modified peptide. The Diels-Alder reaction proceeds with near-quantitative yields in aqueous solution with stoichiometric amounts of reactants, even at low micromolar concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Jäschke et al showed that this polymerase could terminally modify RNA, using norbornene-and BCNmodified guanosine monophosphate (GMP) as the initiator nucleotides. 178,182 A related approach by Royzen et al showed that a cytidine triphosphate (CTP) analogue with a TCO group at the 5-position of the nucleobase is recognized by the T7 RNA polymerase, and therefore is internally and site-specifically incorporated in a RNA strand. 183 Another alternative method for RNA modification uses an engineered methyltransferase that recognises S-adenosyl-L-methionine analogues containing reactive handles and transfers these handles to a RNA of interest (Fig.…”
Section: Alternative Enzymatic Methods or Enzyme Tags For Protein Modmentioning
confidence: 99%
“…Jäschke et al showed that this polymerase could terminally modify RNA, using norbornene-and BCNmodified guanosine monophosphate (GMP) as the initiator nucleotides. 178,182 A related approach by Royzen et al showed that a cytidine triphosphate (CTP) analogue with a TCO group at the 5-position of the nucleobase is recognized by the T7 RNA polymerase, and therefore is internally and site-specifically incorporated in a RNA strand. 183 Another alternative method for RNA modification uses an engineered methyltransferase that recognises S-adenosyl-L-methionine analogues containing reactive handles and transfers these handles to a RNA of interest (Fig.…”
Section: Alternative Enzymatic Methods or Enzyme Tags For Protein Modmentioning
confidence: 99%
“…Traditionally the most common post-labelling chemistry has involved coupling dye succinimidyl esters to amino-modified DNA ( 10 , 11 ). More recently the highly efficient copper catalysed alkyne-azide cycloaddition reaction (CuAAC) ( 12 16 ), strain-promoted alkyne-azide cycloaddition reaction (SPAAC) ( 17 21 ), Diels-Alder (DA) and inverse electron demand Diels-Alder (IEDDA) reaction ( 19 , 22 24 ) have been used. Of these reactions, the SPAAC reaction between cyclooctyne and azide is a good choice because it is fast, orthogonal to the functional groups in DNA, it does not require metal catalysts (which can lead to DNA degradation if not carried out with care) and it involves the non-bulky azide group.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] In particular, the Diels-Alder reaction with inverse electron-demand (DAR inv ) [20][21][22] between numerous dienophiles [23][24][25] and tetrazines 21,26,27 was found to be a valuable tool for effective bioorthogonal conjugations. [28][29][30] Followed by a retro-Diels-Alder reaction to eliminate nitrogen gas, this so-called tetrazine ligation is characterized by extremely fast kinetics with second-order rate constants up to 2 Â 10 3 M À1 s À1 and has been already used in a number of both in situ and in vivo studies. 25,31,32 In this study we present a modular approach to the conjugation of biomolecules based on the combination of two efficient chemical transformations, oxime ligation and DAR inv .…”
mentioning
confidence: 99%